The Fanconi Anemia Ortholog FANCM Ensures Ordered Homologous Recombination in Both Somatic and Meiotic Cells in Arabidopsis([W]) - Knoll, Alexander (American Society of Plant Biologists, 2012)
The human hereditary disease Fanconi anemia leads to severe symptoms, including developmental defects and breakdown of the hematopoietic system. It is caused by single mutations in the FANC genes, one of which encodes the DNA translocase FANCM (for Fanconi anemia complementation group M), which is required for the repair of DNA interstrand cross-links to ensure replication progression. We identified a homolog of FANCM in Arabidopsis thaliana that is not directly involved in the repair of DNA lesions but suppresses spontaneous somatic homologous recombination via a RecQ helicase (At-RECQ4A)–independent pathway. In addition, it is required for double-strand break–induced homologous recombination. The fertility of At-fancm mutant plants is compromised. Evidence suggests that during meiosis At-FANCM acts as antirecombinase to suppress ectopic recombination-dependent chromosome interactions, but this activity is antagonized by the ZMM pathway to enable the formation of interference-sensitive crossovers and chromosome synapsis. Surprisingly, mutation of At-FANCM overcomes the sterility phenotype of an At-MutS homolog4 mutant by apparently rescuing a proportion of crossover-designated recombination intermediates via a route that is likely At-MMS and UV sensitive81 dependent. However, this is insufficient to ensure the formation of an obligate crossover. Thus, At-FANCM is not only a safeguard for genome stability in somatic cells but is an important factor in the control of meiotic crossover formation.